Pengembangan Media Canva berbasis Video Animasi Materi Ekosistem untuk Siswa Sekolah Dasar - Purba, Sonia Erika Ullyartha; Armelia, Alvina; Wulandari, Efri (Indonesian Journal of Science, Technology, Engineering, Art, and Mathematics Education, 2024)
This study aims to develop Canva media based on animated video of ecosystem material for elementary school students. The research method used is research and development with the ADDIE model (analyse, Design, Develop, Implement, and Evaluate). The design developed was tested on a limited basis with students at an elementary school in Pekanbaru. The results of this study indicate that the media used can increase the motivation, interest and learning outcomes of elementary school students. The implication of this study is that teachers need to teach innovatively, namely by using animated video media.